An Improved Composite Fly Ash Gel to Extinguish Underground Coal Fire in Close Distance Coal Seams: A Case Study - Jun Guo; Guobin Cai; Yan Jin; Xuezhao Zheng; Yin Liu (Advances in Materials Science and Engineering)
Fire extinguishing with the superior performance of fly ash composite colloid material is a cost-effective colloid fire prevention technology. In this paper, a new powder additive (suspending agent (XK-XJ) and gelling agent) was developed for the existing fire extinguishing technology of fly ash compound colloid. Tests show that the best additions to the fly ash slurry were 0.3% and 0.1∼0.3%, respectively. The grouting technical scheme of adding a suspending agent on the ground and gelling agent downhole was proposed to solve the problems of solid material settlement and blockage in the long-distance pipeline transportation process. Finally, the optimized fly ash colloid fire prevention and extinguishing technology was successfully applied to the fire control engineering examples of close-range coal seam groups, and the rationality of the developed powder and its proportion was tested, and the feasibility in coal fire control was tested.